The interaction of tectonics, climate and eustasy in controlling dolomitization: A case study of Cenomanian–Turonian, shallow marine carbonates of the Iberian Basin. Issue 5 (2nd March 2020) - Newport, Richard; Segura, Manuel; Redfern, Jonathan; Hollis, Cathy
Abstract: During the Cretaceous, high global sea‐level and low latitudinal temperature variations led to the growth of epeiric carbonate platforms. Platform‐scale dolomitization of these platforms is not common, reflecting the low Mg/Ca ratio of seawater and a humid climate. This study describes the processes governing pervasive dolomitization of a land‐attached carbonate platform within the Iberian Basin. Dolomite is planar to sub‐planar with a geochemical signature consistent with dolomitization from penesaline seawater. Dolomitization was most pervasive during a 1 Myr period in the middle Cenomanian, by repeated reflux of seawater from brine pools formed on the top of a southward‐prograding carbonate platform. Tilting and structural reorganization in the Upper Cenomanian led to a reversal in polarity of the platform, and dolomitization was restarted by the northward reflux of seawater. Rising relative sea‐level and oceanic acidification led to back‐stepping of the platform such that the supply of dolomitizing fluids was cut off. In the Lower Turonian, pervasively dolomitized rudist rudstone facies in the south of the study area indicate that dolomitization restarted, either penecontemporaneously or later, from highly evaporated Campanian–Maastrichtian seawater. A systematic increase in dolomite crystal size up‐section ties broadly, but not entirely, to stratigraphy. It is possible that these textural differences reflect changes in fluid chemistry, limestone permeability or precursor rock texture. However, the lack of stratigraphic conformance, and the preservation of the earliest‐formed dolomite only in the oldest sediments, could indicate a progressive recrystallization of early‐formed dolomite through repeated reflux of brines. As such, the succession appears to preserve a fossilized record of dolomite recrystallization through time during the Cenomanian–Turonian. The results of this study therefore provide a record of the progressive dolomitization of a carbonate platform and demonstrate the important interplay of climate and basin‐scale tectonics on dolomite distribution and crystallinity.